Fully Inkjet-Printed Flexible Graphene–Prussian Blue Platform for Electrochemical Biosensing - Željka Boček; Marko Zubak; Petar Kassal (Biosensors)
Prussian Blue (PB) is commonly incorporated into screen-printed enzymatic devices since it enables the determination of the enzymatically produced hydrogen peroxide at low potentials. Inkjet printing is gaining popularity in the development of electrochemical sensors as a substitute for screen printing. This work presents a fully inkjet-printed graphene–Prussian Blue platform, which can be paired with oxidase enzymes to prepare a biosensor of choice. The graphene electrode was inkjet-printed on a flexible polyimide substrate and then thermally and photonically treated with intense pulsed light, followed by inkjet printing of a PB nanoparticle suspension. The optimization of post-printing treatment and electrode deposition conditions was performed to yield a platform with minimal sheet resistance and peak potential differences. A thorough study of PB deposition was conducted: the fully inkjet-printed system was compared against sensors with PB deposited chemically or by drop casting the PB suspension on different kinds of carbon electrodes (glassy carbon, commercial screen-printed, and in-house inkjet-printed electrodes). For hydrogen peroxide detection, the fully inkjet-printed platform exhibits excellent sensitivity, a wider linear range, better linearity, and greater stability towards higher concentrations of peroxide than the other tested electrodes. Finally, lactate oxidase was immobilized in a chitosan matrix, and the prepared biosensor exhibited analytical performance comparable to other lactate sensors found in the literature in a wide, physiologically relevant linear range for measuring lactate concentration in sweat. The development of mediator-modified electrodes with a single fabrication technology, as demonstrated here, paves the way for the scalable production of low-cost, wearable, and flexible biosensors.